Legal Anthropology - Toivanen, Reetta (2024)
Anthropology is an empirically grounded discipline that bases its science on long-term ethnography and has a unique capacity to understand power and governance over time. Anthropologists are interested in describing all aspects of human reality, including its rules, norms, laws and systems of governance. Legal anthropologists have served as experts on Indigenous peoples’ cultures and traditions, especially in land claims cases. Often, anthropologists have assumed the role of cultural “interpreters” between the Indigenous peoples and governments’ judicial institutions. The Arctic Indigenous peoples live on lands that are of great economic interest to global extractive industries. Governments controlling these areas are reluctant to grant the peoples any land rights. In this contribution, I will first introduce legal anthropology as a discipline and then analyse what has been the special interest of legal anthropologists in the Arctic region. I will also discuss my own research as one way of analysing how Indigenous peoples’ rights affect the Indigenous people of the Fenno-Scandinavian Arctic. I argue that Indigenous peoples’ rights must be studied as “travelling concepts”, ones that change their meaning from one place to another. This means that Indigenous rights must be examined as a multi-layered, complex, often even self-contradictory body of law. Peer reviewed